2004
DOI: 10.1111/j.1365-2214.2004.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

How great is the risk of abuse in infants born to drug‐using mothers?

Abstract: Maternal drug use does not necessarily lead to unacceptable standards of parenting. More UK-based research is needed to inform the risk assessment process for child protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
3
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 9 publications
0
14
3
1
Order By: Relevance
“…Around 25% of all children subject to a child protection plan are cared for by a parent with a substance misuse problem [5] and one study found a significantly higher risk of child protection proceedings amongst infants of substance-misusing parents compared with infants of non-drug users (32.4% vs. 7.1%) [6]. These figures are similar for other countries such as the US [7,8] and Australia [9].…”
Section: Introductionmentioning
confidence: 92%
“…Around 25% of all children subject to a child protection plan are cared for by a parent with a substance misuse problem [5] and one study found a significantly higher risk of child protection proceedings amongst infants of substance-misusing parents compared with infants of non-drug users (32.4% vs. 7.1%) [6]. These figures are similar for other countries such as the US [7,8] and Australia [9].…”
Section: Introductionmentioning
confidence: 92%
“…The medical consequences of substance abuse during pregnancy are well documented (Hepburn, 2004) and there is an increased risk of child protection proceedings in the first 18 months of the infants life (Street et al, 2004). Indeed, in one study, 32 out of 1306 children living with known substance abusing parents were on the social services Child Protection Register in Scotland (Murray, 2003).…”
Section: Mental Health Difficulties Substance Abuse and Child Abusementioning
confidence: 97%
“…In a community-based study, 47% of drug addicts had responsibility for at least one child under the age of 18 years (Gossop et al, 1998). Furthermore, rates of domestic violence amongst substance abusing pregnant women would appear to be particularly high (Velez et al, 2006).…”
Section: Mental Health Difficulties Substance Abuse and Child Abusementioning
confidence: 99%
“…Recent work by Taplin and Mattick (2013)) found that of 171 women who were all receiving opiate substitution therapy, almost one third (32.7%) had a child living in OOHC. Whilst maternal (or paternal) substance use does not necessarily lead to poor parenting (Street, Harrington, Chiang, Cairns, & Ellis, 2004), it is strongly linked to child maltreatment and neglect (Blakey, 2012). Mothers with a history of a SUD are often highly involved with the child protection system, highlighting the vulnerabilities of these family units (Schilling, Mares, & El-Bassel, 2004;Taplin & Mattick, 2013).…”
Section: Introductionmentioning
confidence: 99%